Fetal Bowel Dilatation: A Sonographic Sign of Uncertain Prognosis - Patrícia Silva; Filipa Reis; Paulo Alves; Luís Farinha; Manuel Sousa Gomes; Pilar Câmara (Case Reports in Obstetrics and Gynecology)
Fetal bowel dilatation is an indirect sonographic sign of mechanical or functional bowel obstruction. The etiology of fetal bowel dilatation is a difficult prenatal diagnosis since ultrasound has limited accuracy for bowel evaluation. The authors describe a case of fetal bowel dilatation diagnosed in the third trimester.